DOMINANT RISK FACTORS CORONARY ARTERY DISEASE IN CARDIAC PATIENTS IN THE CARDIAC CLINIC OF THE HOSPITAL BENGKULU PROVINCE: CORONARY ARTERY DISEASE - Ratnadhiyani, Anditha; Wulandari, Dwi; Hermansyah, Hermansyah (STIKes Mandala Waluya Kendari, 2024)
Background: Coronary artery disease (CAD) is one of the leading cardiovascular diseases and the number one cause of death in the world. World Health Organization (2020) Non-communicable diseases (NCDs), which are the leading cause of death worldwide, are cardiovascular diseases. In 2017 an estimated 17.9 million people (31% of all deaths) died from cardiovascular disease. Methods: The research design used This research design is an analytic observational using a Cross-Sectional research design that will be conducted at the RSMY Heart Poly, in June-August 2024. The number of samples in this study were 100 respondents who fit the inclusion criteria of the researchers. The analysis used in this study is to use bivariate, univariate and multivariate analysis in finding the riskiest factors. Results: The results showed that there was an association between age, gender, occupation, family history) obesity, hypertension, diabetes mellitus, hyperlipidemia, smoking, physical activity with the incidence of coronary artery disease (CAD) in cardiac patients at the cardiac clinic of RSMY Hospital Bengkulu Province, with a P value <0.05, while the most dominant factor causing CAD was diabetes mellitus disease factor. Conclusion: The results showed that the dominant risk factors affecting the quality of life of CAD patients in the Cardiology Clinic of RSUD Dr. M. Yunus Bengkulu Province were diabetes mellitus, followed by hypertension and smoking. This study provides important insights for the development of CAD prevention and management programs in the community.